PENGARUH MODEL PROBLEM BASED LEARNING (PBL) TERHADAP MINAT BELAJAR PESERTA DIDIK PADA PEMBELAJARAN IPAS KELAS III SEKOLAH DASAR NEGERI 3 LANGSA - Nurmasitah; Dini Ramadhani; Muhammad Febri Rafli (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to determine the effect of implementing the Problem-Based Learning (PBL) model on students’ interest in learning Natural and Social Sciences (IPAS) in the third grade at Langsa 3 Public Elementary School. The background of this study is based on the low level of student interest in learning, caused by the use of conventional teaching models, which results in students being less active and easily bored during the learning process. This study employs a quantitative approach using a posttest-only control group design. The population consists of all 40 third-grade students at Langsa State Elementary School 3, with the sample comprising Class IIIA as the experimental group and Class IIIB as the control group. Data collection utilized a learning interest questionnaire with a Likert scale that had been tested for validity and reliability. Data analysis was conducted using an independent samples t-test. The results indicate that students’ learning interest in third-grade IPAS instruction at Langsa State Elementary School 3 is significantly influenced by the implementation of the PBL model. The average score for the experimental class that implemented the PBL model was 55.35, while the score for the control class was 43.80. Therefore, the Problem-Based Learning (PBL) model can be considered a better alternative.